Estimating a structural model of herd behavior in financial markets - Marco Cipriani; Antonio Guarino (Federal Reserve Bank of New York, 2012)
We develop a new methodology for estimating the importance of herd behavior in financial markets. Specifically, we build a structural model of informational herding that can be estimated with financial transaction data. In the model, rational herding arises because of information-event uncertainty. We estimate the model using 1995 stock market data for Ashland Inc., a company listed on the New York Stock Exchange. Herding occurs often and is particularly pervasive on certain days. In an information-event day, on average, 2 percent (4 percent) of informed traders herd-buy (sell). In 7 percent (11 percent) of information-event days, the proportion of informed traders who herd-buy (sell) is greater than 10 percent. Herding causes important informational inefficiencies, amounting, on average, to 4 percent of the asset's expected value.
Keywords: G14; D82; C13; 330; herd behavior; market microstructure; structural estimation